2012
DOI: 10.1007/s10120-012-0155-4
|View full text |Cite
|
Sign up to set email alerts
|

Incidence trends and mortality rates of gastric cancer in Israel

Abstract: Background Gastric cancer is the fourth most common malignancy worldwide. The incidence trends and mortality rates of gastric cancer in Israel have not been studied in depth. The aim of our study was to try and investigate the aforementioned issues in Israel in different ethnic groups. Methods This retrospective study is based on the data of The Israel National Cancer Registry and The Central Bureau of Statistics. Published data from these two institutes were collected, summarized, and analyzed in this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…3 Although most studies suggest a positive association between the BMI and cancer of the gastric cardia (CGC), 4-7 data from meta-analyses have indicated no association between obesity and noncardia gastric cancer (NCGC). 8 In Israel, the age-standardized incidence declined to a rate of 9.7 per 100,000 in 2012, 9,10 with a high incidence of gastric cancer among immigrants from the former Soviet Union (FSU). 8 In Israel, the age-standardized incidence declined to a rate of 9.7 per 100,000 in 2012, 9,10 with a high incidence of gastric cancer among immigrants from the former Soviet Union (FSU).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Although most studies suggest a positive association between the BMI and cancer of the gastric cardia (CGC), 4-7 data from meta-analyses have indicated no association between obesity and noncardia gastric cancer (NCGC). 8 In Israel, the age-standardized incidence declined to a rate of 9.7 per 100,000 in 2012, 9,10 with a high incidence of gastric cancer among immigrants from the former Soviet Union (FSU). 8 In Israel, the age-standardized incidence declined to a rate of 9.7 per 100,000 in 2012, 9,10 with a high incidence of gastric cancer among immigrants from the former Soviet Union (FSU).…”
Section: Introductionmentioning
confidence: 99%
“…8 In Israel, the age-standardized incidence declined to a rate of 9.7 per 100,000 in 2012, 9,10 with a high incidence of gastric cancer among immigrants from the former Soviet Union (FSU). 9 In light of the increasing prevalence of adolescent obesity in Israel, 2,12,13 concern about gastric cancer among immigrants from the FSU, 11 and a report on the association of the BMI with NCGC, 8 we expanded our previous research on the association between the measured BMI, country of birth, and residential socioeconomic status (SES) in adolescence and the risk of gastric cancer among men. 9 In light of the increasing prevalence of adolescent obesity in Israel, 2,12,13 concern about gastric cancer among immigrants from the FSU, 11 and a report on the association of the BMI with NCGC, 8 we expanded our previous research on the association between the measured BMI, country of birth, and residential socioeconomic status (SES) in adolescence and the risk of gastric cancer among men.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The M/I of stomach cancer was 2.56‐fold higher in Shandong than in Korea (0.69/0.27). The Incidence and mortality of stomach cancer were also much higher in Shandong Province than in other countries in Asia, such as Iran, Israel, and Bhutan . This indicated that the situation of stomach cancer control and prevention was very serious, and measures taken to improve cancer survival rates and reduce mortality were also important in Shandong Province.…”
Section: Discussionmentioning
confidence: 99%
“…Although the incidence and mortality rates have declined worldwide, as the most common cancer, gastric cancer (GC) still ranks fourth in incidence and second in annual cancer-related deaths [1]. Approximately 70% of new cases and deaths occur in developing countries, and the number of Chinese GC patients(pts) accounts for 35-42% of cases worldwide [2,3].…”
Section: Introductionmentioning
confidence: 99%